Connecticut SNAP 2019 - Kinkead, Gwen, (SAGE business cases., 2020)
Connecticut's $570 million food stamp program administered by the Connecticut Department of Social Services had long been ranked one of the worst in the nation until the attention of Roderick Bremby. Under Bremby's leadership, Connecticut's Supplemental Nutrition Assistance Program (SNAP) became of the nation's best helping those near or below the poverty level to put food on the table. The case describes the improvements that Bremby implemented and the challenges and dilemmas faced by the Connecticut Department of Social Services.